2015
DOI: 10.1021/acs.joc.5b01949
|View full text |Cite
|
Sign up to set email alerts
|

Reactions of 1,3-Diketones with a Dipeptide Isothiazolidin-3-one: Toward Agents That Covalently Capture Oxidized Protein Tyrosine Phosphatase 1B

Abstract: Protein tyrosine phosphatase 1B (PTP1B) is a validated therapeutic target for the treatment of type 2 diabetes; however, the enzyme has been classified by some as an "undruggable target". Here we describe studies directed toward the development of agents that covalently capture the sulfenyl amide "oxoform" of PTP1B generated during insulin signaling events. The sulfenyl amide residue found in oxidized PTP1B presents a unique electrophilic sulfur center that may be exploited in drug and probe design. Covalent c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 41 publications
1
11
0
Order By: Relevance
“…4C). 25, 57 Owing to poor reaction rate, 7a failed to capture Gpx3-SOH, a finding that was consistent with data obtained in the dipeptide-SOH model (Fig. 4D).…”
Section: Resultssupporting
confidence: 88%
“…4C). 25, 57 Owing to poor reaction rate, 7a failed to capture Gpx3-SOH, a finding that was consistent with data obtained in the dipeptide-SOH model (Fig. 4D).…”
Section: Resultssupporting
confidence: 88%
“…The molecular factors that control formation of sulfenyl amides are still unclear, but recent computational studies suggest that a constrained cysteine conformation within a β-loop-helix fold motif favors sulfenyl amide formation from initially generated Cys-SOH. [71] Importantly, recent studies using model sulfenyl amide compounds indicated that several dimedone-based reagents used to detect Cys-SOH are also reactive towards sulfenyl amides [26, 72], indicating that detection of dimedone-reactive proteins does not necessarily reflect the presence of Cys-SOH but may also indicate sulfenyl amides. Therefore, dimedone or chemically similar compounds are best considered molecular probes of for “two-electron oxidized cysteine species” representing either Cys-SOH or sulfenyl amides.…”
Section: Chemical Detection Of Sulfenic Acid: Is It In Fact Sulfenmentioning
confidence: 99%
“…Moreover, substitution by highly EWGs, such as –CF 3 , may lead to hydration of the carbonyl and complete loss of reactivity due an increase in C-3 carbanion p K a). 15 Subsequently, for nucleophiles of structural class 4 and 5 we postulated that replacing one or both carbonyls with a carboxylate ester, amide or hydrazide functionality would increase the p K a of the nucleophilic C-centre. Consistent with this hypothesis, we observed a marked decrease in reactive carbanion formation at physiological pH and a corresponding reduction in reactivity (Fig.…”
mentioning
confidence: 99%